Credit behavior of households: structural and analytical aspects - KIZYMA, Tetiana (Scientific journal «World of Finance», 2019)
Introduction. Under modern conditions, Ukrainian households are increasingly trying to follow Western models of financial behavior, in which, due to stable laws and monetary-financial system, citizens demonstrate active credit behavior. At the same time, it should be noted that during the recent years the number of users of bank loans in Ukraine, who have overdue debts, has increased rapidly, that cause concern among domestic scientists and practitioners. Purposeof the research is to analyses the modern trends in households’ credit behavior in Ukraine and development of proposals for its rationalization under the current circumstances. Results. Under modern conditions, each household forms its own model of credit behavior, taking into account certain factors, established traditions and beliefs regarding the appropriateness of borrowing funds. However, an important feature of credit dependence of our nationals is still lack of critical analysis of their own financial capabilities due to their inability to resist the natural desire of a person to “live now” and “live well”. The study showed that over the past ten years, from 8% to 16% of the adult population of Ukraine took credits in the banks. Moreover, the Western region is the leader in bank borrowings (with the exception of credit cards), while Kyiv, the North and the East show a higher level of credit card loans. Kyiv and the East are also characterized by higher demand for pawnshops. The Centre is the only region with relatively more frequent use of services of other financial institutions. Also, the practice of providing (obtaining) of so-called non-institutional credits is common among Ukrainian households, when citizens are not only borrowers but also creditors (that is, situations when relatives, friends, acquaintances are borrowing money). Conclusions. Under the context of current financial crisis in Ukraine, the role of the state, local governments, institutions and individuals in rationalizing households’ lending behavior is significantly increasing. Therefore, in our opinion, preventive measures in this sphere should be carried out at the following levels: state, local, banking and financial-credit system, and personally-individual. At the same time, it should be emphasized that these measures will be implemented only if the state provides clear legal regulation of the credit process and establishes trust relations with the population, which will help to minimize the moral and material losses of households and institutional subjects of credit activity.